2001
DOI: 10.1002/0471141755.ph0308s13
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Enzymatic Assays of Protein Tyrosine Phosphatase 1B

Abstract: Many hormone or growth factor receptors signal via the activation of protein-tyrosine kinases and phosphatases. Alteration of the phosphorylation state of tyrosine residues in certain proteins can directly regulate enzyme activity or cause formation of protein complexes necessary for transducing intracellular signals. Genetic and biochemical evidence also implicates protein-tyrosine phosphatases in several disease processes, including negative regulation of insulin receptor signaling at the level of the insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…tpbA encodes a 218 aa protein that has the conserved domain for a protein tyrosine phosphatase [28] , [29] since it has the C(X) 5 R(S/T) motif beginning at aa 132 ( C KHGNN RT ). To confirm it is a tyrosine phosphatase, we purified TpbA by adding a polyhistidine tag at either the N-terminus (TpbA-nHis) or the C-terminus (TpbA-cHis) (note only the C-terminus fusion protein was active).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…tpbA encodes a 218 aa protein that has the conserved domain for a protein tyrosine phosphatase [28] , [29] since it has the C(X) 5 R(S/T) motif beginning at aa 132 ( C KHGNN RT ). To confirm it is a tyrosine phosphatase, we purified TpbA by adding a polyhistidine tag at either the N-terminus (TpbA-nHis) or the C-terminus (TpbA-cHis) (note only the C-terminus fusion protein was active).…”
Section: Resultsmentioning
confidence: 99%
“…6A ). The purified TpbA protein had phosphatase activity with p -nitrophenyl phosphate (pNPP) that is often used as a general phosphatase substrate [29] ( Fig. 6B ).…”
Section: Resultsmentioning
confidence: 99%
“…The results were shown in Table 6. Notably, 3 c , 3 j , and 3 o showed approximately four times stronger inhibitory activities towards PTP1B enzyme than compound 9 j and more than double potency of ursolic acid, [9] a known inhibitor of PTP1B. The results suggested that this class of compounds could be developed as potential PTP1B inhibitors.…”
Section: Resultsmentioning
confidence: 92%
“…In this work, an ingenious method was reported for the construction of arylnaphthenelactone 3 using ortho ‐alkynylarylketones 8 as the starting material. Substrate 8 could be prepared from inexpensive and readily available dimethyl malonate 7 which could be easily functionalized at R 3 to increase the diversity of the desired products [7] . Previously, our research group reported the synthesis of naphthofurans 5 and 6 using ortho ‐alkynylarylketones 4 as the starting material [5d] .…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme activity was estimated by measuring the absorbance at 405 nm with appropriate corrections. Each experiment was performed in triplicate, and IC 50 data were derived from three independent experiments [34].…”
Section: Ptp1b Inhibitory Assaymentioning
confidence: 99%